DEKOMPOSISI GRAF MATAHARI - Musthofa, Putri Rizqi; Kuswardi, Yemi (Journal of Mathematics and Mathematics Education, 2018)
Abstract:Graph theory is a branch of mathematics that facilitates problem solving. There are a lot of researches which concern on this issue. Various kinds of terms are introduced, one of them is graph decomposition. Graph decomposition is sub graphs collection of non-empty G graph Hi until Hi = 〈Ei〉 for non-empty sub graph Ei of E (G), where Ei is a partition of E (G). Sub graph Hi in decomposition G do not contain of isolated points. If Hi is a decomposition of G, it is denoted by .The discussion of graph decomposition can be developed in graph decomposition through various types. One of the types is decomposition of sun graphs. Sun graph is a graph formed from a circle Cn in which each vertex on a circle graph is given one additional vertex with a degree. So, each vertex in sun graph has 3 degrees, except the edge of cortex which only have 1 degree. The sun graph is the result of corona between two graphs, namely a circular graph with n vertex and complement of a complete graph with 1 number of vertex . The sun graph is denoted by where n is the number of vertex in circle graph. If the vertex naming refers to one vertex (with clockwise rules) and additional vertex naming connected to a circle vertex graph (vi), where the additional vertex has a degree of one, then the rule of naming is and sun graph is partitioned into a sub graph H_i = 〈Ei〉 in the form of K2 where i ≠ j so that H_i∩H_j = ∅, for i = 1,2,3, ..., n with sub graph If every i + 1, i + 2> n has an implicit + 1 and i + 2 will be expressed as an integers 1,2,3, ..., n (mod n), then the sun graph is 2K2-decomposition. So, for sun graph n ≥3 is 2K2-decomposition.Keywords:Decomposition, Sun Graph.